Using design thinking to support the IoC Process. - Whitsed, Craig; Leask, Betty (Universidad de Guadalajara Press, 2022)
This chapter argues augmenting the curriculum internationalization process described by Leask (2013, 2015) with design thinking approaches, tools, and resources has the potential to enhance the IoC process. This is done with reference to the use of design thinking to guide the development of a Postgraduate Certificate in Higher Education Innovative Teaching and Learning at Curtin University in Perth, Australia. The synergies between design thinking and Leask’s (2015) IoC Process are discussed using examples from the postgraduate certificate to highlight the value of using design thinking to address the complex problem of curriculum design in general and internationalization of the curriculum specifically. The chapter concludes with a reflection on the potential for design thinking to enhance the process of curriculum internationalization.